Developing An Inclusive Culture Through “Utari Sendakeb” At UPT SD Negeri 263 Gresik - Badrut Tamam; Yatim Riyanto; Erny Roesminingsih (International Conference on Elementary Education, 2023)
One of the efforts to create a comfortable and friendly school social environment at the Inclusive Education Provider School (SPPI) is to develop an inclusive culture at the school. In fact, an inclusive culture at UPT SD Negeri 263 Gresik has not materialized or has not been developed properly. This is indicated by the continued bullying attitude towards Children with Special Needs (ABK) by regular students and some students do not want to associate or interact with ABK. This study aims to identify and describe the inclusive culture developed by UPT SD Negeri 263 Gresik through "Utari Sendakeb" in order to create a comfortable and friendly school environment. The method used in this research is a qualitative research method with a case study type of research. The informants were school principals, teachers, regular students, students with special needs, and parents/guardians of UPT SD Negeri 263 Gresik students. Meanwhile, data collection techniques used in-depth interviews with informants, participant observation, Forum Group Discussion (FGD), and documentation studies. Based on the data collected, it is known that through habituation activities in the morning before the teaching and learning process begins, "Utari Sendakeb" namely Ceremony, Tartil Al Quran, Self Evaluation, Gymnastics, and Community Service, an inclusive culture at UPT SD Negeri 263 Gresik can be realized or developed well. This is indicated by the school community having implemented inclusive cultural values ​​well. However, there are indicators of inclusive cultural values ​​that need to be developed and become program priorities in the future, namely the indicators that everyone feels welcome at school and that everyone must have the character of caring, empathy and helping each other.